Customized Virtual Simulations Provide an Interactive Lab Experience - Meredith O. Sweeney; Johanna E. Farkas; Erica P. Homan; Desislava (Dessy) A. Raytcheva (Journal of Microbiology & Biology Education, 2022)
ABSTRACT Although various resources exist for facilitating online laboratory courses, stitching together disparate elements from multiple sources may not be sufficient to meet the learning goals of a given course. For example, our Biology Project Lab course introduces students to an array of fundamental laboratory techniques, and the COVID-19 pandemic necessitated the development of virtual laboratory options for remote learners. We anticipated that the logic and application of the course material—a multiday sequence of connected experiments—would be lost if we combined prefabricated labs from a variety of sources. Moreover, we wanted students to familiarize themselves with our laboratory equipment, while providing interactive experiences rather than passive video demonstrations. Therefore, we used Storyline 360 to create a series of interactive lab modules to accommodate students who were remote or in quarantine. These online labs were integrated with our learning management system (LMS) and included exercises such as video demonstrations, short answer responses, image selection, drag-and-drop activities, and organizing procedural steps. Our simulations can be shared with instructors and customized for their own interactive labs, or instructors can build course-specific modules from scratch using the Storyline 360 platform. Although the simulations could not fully replicate the in-person learning experience, students appreciated being able to watch and participate in lab activities and recommended that the labs be retained as supplemental activities in future semesters. Storyline 360 thus offers an effective platform for developing virtual laboratory modules which may be widely adapted to suit the specific needs of a variety of laboratory courses.